Hospitality students satisfaction towards blended learning in Universiti Malaysia Kelantan - Nur Haleeza Hanim Abdul Rahman; Siti Suraya Sho’ib; Elfiyana Irwan; Savitrie Wi Nai (2021)
This study was undertaken in order to examine hospitality student’s satisfaction towards blended learning engagement in Universiti Malaysia Kelantan. This research examines the relationship between determinants which are perceived playfulness, perceived usefulness, perceived ease of use and blended learning engagement hospitality student’s satisfaction in Universiti Malaysia Kelantan. To further understand the relationship between the student’s satisfactions of blended learning, a quantitative approach was employed. An online survey was collected among year 1, 2, 3 and 4 hospitality students in Universiti Malaysia Kelantan. The data collected was analysed by using descriptive and Pearson’s correlation analysis techniques. 239 responses were received. The findings showed that the three variables which are perceived playfulness, perceived usefulness and perceived ease of use are significantly related to blended learning engagement hospitality students satisfaction. Lastly, some other determinants are recommended to include for further research to explore and acquire further reasoning.